Spatial morphology of canal residences from the perspective of cultural ecology: insights from the Yaowan Ancient Town in northern Jiangsu province, China - Chang Ding; Xiang Chen; Ziyi Wang (Journal of Asian Architecture and Building Engineering)
The traditional residential architecture of Northern Jiangsu embodies a unique blend of southern and northern architectural styles, showcasing distinctive qualities and characteristics with significant artistic, cultural, and historical value. This architectural form not only serves as a material carrier of regional culture but also represents the product of long-term interactions between the unique social and historical context and the natural environment along the northern Jiangsu Canal. With the wave of urbanization, the canal residences in northern Jiangsu have been significantly impacted in the aspect of spatial texture and cultural continuity. From the perspective of cultural ecology, this paper takes Yaowan Ancient Town, which is located along the Northern Jiangsu Canal in China as a case study. Through literature analysis, map analysis, field investigation, interviews, and statistical methods, it provides an in-depth interpretation of its cultural ecological environment. The study reveals the interactions among canal culture, the natural environment, and the spatial form of architecture, and summarizes the characteristic patterns of spatial morphology in residential buildings along the northern Jiangsu Canal. Finally, this paper proposes development recommendations from a cultural ecological perspective to enhance the preservation of northern Jiangsu Canal residences and promote the adaptive development of canal culture.